Queen Elizabeth II - Davidson, Susanna; Designed by Tomlins, Karen (London Usborne Publishing, 2012)
A biography of the Queen, from her birth to the present day. It includes photographs, a family tree and a timeline.
Include Color Illustration
Keywords: Queens -- Great Britain -- Elizabeth II, Queen of Great Britain, 1926-